Open access central funds in UK universities - Pinfield, Stephen; Middleton, Christine (ALPSP, 2012)
This paper reports on the extent to which higher education institutions in the UK have set up central funds and similar institutionally co-ordinated approaches to the payment of open access article-processing charges. It presents data demonstrating that central funds have only been set up by a minority of institutions and that the number of institutions has not changed significantly between 2009 and 2011. It then explores the barriers to the establishment of such funds and discusses recent developments that might lower these barriers. Finally, it provides a case study of the development of the central fund at the University of Nottingham in the UK and considers the sustainability of such an approach.